Deteksi Kandungan Formalin dan Boraks pada Bakso Daging yang dijual Di Kota Kefamenanu - Marianus Nahak Seran; Stefanus Sio; Kristoforus W. Kia (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
This study aims to detect the presence of Formalin and borax in meatballs sold in Kefamenanu City. This research was conducted by taking 20 samples of meatballs at stalls selling meatballs. Testing of Formalin and borax on meatballs was carried out qualitatively. Testing the borax content in meatballs was carried out by looking at the color changes that occurred in the residue from the addition of 0.125% curcumin to the supernatant. If the residue is cherry red, the borax is positive. Qualitative testing of Formalin on meatballs was carried out by observing the color change with the addition of chromofatic acid, phosphoric acid, and hydrogen peroxide to the filtrate. If there is a color change to purplish red, the sample is positive for Formalin. The test data obtained were analyzed using descriptive statistical tests in the form of percentage values. The results showed that from 20 samples of meatballs tested; there was no formalin and borax. It was concluded that the producers or sellers of meatballs in Kefamenanu City, North Central Timor Regency did not use borax as a meatball thickener and Formalin as a preservative in the manufacture of meatballs.